Culture and customs of the Caucasus - Roudik, Peter (Westport, Conn. : Greenwood Press, 2009)
From the Publisher: In the early 1990's, Armenia, Azerbaijan, and Georgia emerged from the grip of the Soviet Union and stood on their own for the first time in almost a century. Today, these three nations are slowly emerging from communism's dark cloud, thriving culturally and gaining strength economically. Culture and Customs of the Caucasus is the ultimate one-stop reference source that explores the three countries in the region-no other reference work provides such comprehensive and current material. Students studying world culture, social studies, and multicultural issues can use this engaging and wide-ranging volume to learn about the Caucasus's history, urban life, religion, literature, cuisine, holidays, and leisure activities, among many other topics.
Series foreword ; Preface ; Chronology ; 1: Land, people, and history ; 2: Urban and rural developments ; 3: Family, marriage, and education ; 4: Thought and religion ; 5: Languages, folklore, and literature ; 6: Food, drinks, and fashion ; 7: Cinema and performing arts ; 8: Visual arts and crafts ; 9: Sport, leisure, and festivals ; Glossary ; Bibliography ; Index.
Includes bibliographical references (p. [193]-198) and index.
Keywords: Caucasus -- Social life and customs; Caucasus -- Civilization; Armenia -- Social life and customs; Azerbaijan -- Social life and customs; Georgia (Republic) -- Social life and customs